Psychosocial and pharmacological interventions for personality disorders in low- and middle-income countries: A systematic review. - Thea Lynne Hedemann; North de Pencier; Terri Rodak; Muhammad Ishrat Husain; Usman Arshad; Farooq Naeem; Nasim Chaudhry; Muhammad Omair Husain (Public Library of Science (PLoS), 2023)
Personality disorders (PDs) have a global prevalence of 7.8% and are associated with increased rates of morbidity and mortality. Most research on PDs has been conducted in High Income Countries (HICs). We conducted a systematic review to investigate the effectiveness of psychosocial and pharmacological interventions for personality disorders (PDs) in individuals from Low- and Middle-Income Countries (LMICs.) We systematically searched MEDLINE, Embase, APA PsycInfo, Web of Science, Cumulative Index of Nursing and Allied Health Literature (CINAHL), and The Cochrane Library from inception to January 5, 2023. Inclusion criteria were quantitative studies and grey literature where participants received a psychosocial or pharmacological intervention for PD. Exclusion criteria were qualitative studies, review articles, studies in which PD was not the primary condition, and articles not available in English. The Cochrane Risk of Bias tool version 2.0 and Joanna Briggs Institute instruments were used to measure risk of bias. Studies were pooled by type of study, PD investigated, type of intervention, assessment methods, and outcomes. Sixteen studies met inclusion criteria and were included. Fifteen were intervention studies related to borderline PD. Only one studied mixed PDs. Twelve studies were of psychotherapy, one pharmacotherapy, one combination of both, and two neurostimulation. Most of the studies showed improvement in symptoms though data was largely collected using self-report measures. There were only six RCTs. There is a dearth of literature on interventions for PDs in LMICs and funding bodies should prioritize research in LMICs. Systematic Review Registration Number: PROSPERO CRD42021233415.